2008
DOI: 10.1523/jneurosci.3399-08.2008
|View full text |Cite|
|
Sign up to set email alerts
|

Control of Motoneuron Survival by Angiogenin

Abstract: Mutations in the hypoxia-inducible factor angiogenin (ANG) have been identified in Amyotrophic Lateral Sclerosis (ALS) patients, but the potential role of ANG in ALS pathogenesis was undetermined. Here we show that angiogenin promotes motoneuron survival both in vitro and in vivo. Angiogenin protected cultured motoneurons against excitotoxic injury in a PI-3-kinase/Akt kinase-dependent manner, whereas knock-down of angiogenin potentiated excitotoxic motoneuron death. Expression of wild-type ANG protected again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
189
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(195 citation statements)
references
References 27 publications
4
189
0
1
Order By: Relevance
“…The level of phosphorylated Akt, the activated form of Akt, is downregulated in motor neurons in autopsied spinal cords of FALS patients and SALS patients, 26 and the activation of the PI3K/Akt prosurvival pathway delays the progression of ALSlinked motor neuron death in vivo. [27][28][29] In this study, consistent with these previous observations, we found that the BTBD10 levels were decreased in the motor neurons of the spinal cords from SALS patients (Figure 5b). Although there was one ALS patient (case 5, see Table 1), whose motor neurons displayed no reduction in the BTBD10 level, the overall findings suggest that reduced expression of BTBD10 may contribute to motor neuron death in most SALS cases by downregulating the Akt-mediated prosurvival signal.…”
Section: Discussionsupporting
confidence: 92%
“…The level of phosphorylated Akt, the activated form of Akt, is downregulated in motor neurons in autopsied spinal cords of FALS patients and SALS patients, 26 and the activation of the PI3K/Akt prosurvival pathway delays the progression of ALSlinked motor neuron death in vivo. [27][28][29] In this study, consistent with these previous observations, we found that the BTBD10 levels were decreased in the motor neurons of the spinal cords from SALS patients (Figure 5b). Although there was one ALS patient (case 5, see Table 1), whose motor neurons displayed no reduction in the BTBD10 level, the overall findings suggest that reduced expression of BTBD10 may contribute to motor neuron death in most SALS cases by downregulating the Akt-mediated prosurvival signal.…”
Section: Discussionsupporting
confidence: 92%
“…13 What are the possible causes of acidosis during motoneuron degeneration in ALS? First, previous findings have implicated the occurrence of local hypoxia/ischemia and blood-spinal cord barrier leakage in the pathophysiology of ALS, 14 events that may lead to metabolic acidosis in the affected tissues. Reduced angiogenesis may also contribute to the pathophysiology of ALS: mutations in hypoxia inducible factor angiogenin are associated with familial and 'sporadic' forms of ALS in humans, 22 while a deletion in the hypoxia response element of the vascular endothelial growth factor (VEGF) gene is sufficient to cause motoneuron degeneration in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Motoneuron survival was assessed using the trypan blue (Sigma-Aldrich, Dublin, Ireland) exclusion method and motoneuron-specific marker, smi-32, as described previously. 14,17 Following the treatment, cultures were incubated in trypan blue (Sigma-Aldrich, Dublin, Ireland) for 5 min, washed in phosphate-buffered saline (PBS) and fixed with 4% paraformaldehyde in 0.1 M PBS. Cells were immunostained with antibodies to smi-32 (1 : 500, Abcam, Cambridge, UK), for motoneuron survival counts, and the neuron-specific marker, neuronal nuclear antigen (NeuN, 1 : 400; Millipore, Cork, Ireland), for total neuronal counts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ANG protects mouse P19 embryonal carcinoma cells (26) and cultured mouse motor neurons from stress-induced apoptosis (27,28). Human motor neurons (hMNs) differentiated from ES cells express the motor neuron markers TUJ1, MAP2, SMI-32, and peripherin ( Fig.…”
Section: Resultsmentioning
confidence: 99%